Evolving methodologies and concepts in 4D nucleome research. (June 2020) - Sparks, Thomas M.; Harabula, Izabela; Pombo, Ana
Abstract: The genome requires tight regulation in space and time to maintain viable cell functions. Advances in our understanding of the 3D genome show a complex hierarchical network of structures, involving compartments, membraneless bodies, topologically associating domains, lamina associated domains, protein- or RNA-mediated loops, enhancer–promoter contacts, and accessible chromatin regions, with chromatin state regulation through epigenetic and transcriptional mechanisms. Further technology developments are poised to increase genomic resolution, dissect single-cell behaviors, including in vivo dynamics of genome folding, and provide mechanistic perspectives that identify further 3D genome players by integrating multiomics information. We highlight recent key developments in 4D nucleome methodologies and give a perspective on their future directions.